Experimental Investigation on the DC Breakdown Strength of Air Under Various Field Uniformities - Murni Irawan, Nurul Iwanina; Kamarudin, Muhammad Saufi (Evolution in Electrical and Electronic Engineering, 2022)
The design and durability of the insulation are important in preventing leakage when electrical stress occurs. Therefore, experimental studies were performed on the electrodes by using the surrounding air as insulation. The breakdown strength of five pairs of electrodes, which are the sphere-sphere electrode, rod-rod electrode, sphere-rod electrode, spherical-plane electrode and the plane-rod electrode was tested at distances of 0.5 cm, 1.0 cm, 1.5 cm, 2.0 cm, 2.5 cm and 3.0 cm. This experiment is divided into two parts, which are positive DC breakdown voltage and negative DC breakdown voltage. Then, simulations were performed using Finite Element Method Magnetics 4.0 (FEMM 4.0) software to obtain the electric field intensity for each electrode pair at different distances and the maximum electric field, Emax. Several calculations were performed to obtain the parameters required in this study. The relationship between Emax and electrode pair distance and breakdown voltage can be studied using the data obtained from the calculation results. The relationship between the field utilization factor and the distance between each electrode pair has also been discussed in this research. At the end of the study, it was found that the sphere-sphere electrode pair produced the highest breakdown voltage which are 73.52 kV and 69.24kV during a positive and negative breakdown, respectively. It also has the lowest Emax value which is 27.488 kV/cm, and the highest field utilization factor (0.98) compared to the other electrode pairs. This indicates that the sphere-sphere electrode pair is the best electrode pair due to its shape having a uniform surface.